D.I. MENDELEYEV ABOUT ROLE OF PROTECTIONISM IN DEVELOPMENT OF INDUSTRY - Кривуц, Ю. Н. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
Vision is expounded an of genius scientist and great patriot of role of doctrine of protectionism on development of domestic industry, foremost its processing industries as necessary condition of economic independence of country and parcel of its financial prosperity, simply certain place in the system of international division of labor and in the band of nations. As one of the patronized measures of D.I. Mendeleyev names the system of customs duties, executing different functions – from protective to the stimulant.